Estimation of gastric pH in cynomolgus monkeys, rats, and dogs using [13C]-calcium carbonate breath test. Issue 9 (September 2016) - Tobita, Kazuki; Inada, Makoto; Sato, Asuka; Sudoh, Kimiyoshi; Sato, Hitoshi
Abstract: Background: The determination of gastric pH is important for the confirmation of efficacy of anti-secretory drugs. However, current methods for measurement of gastric pH provide significant stress to animals and humans. Aim: The objective of this study is to establish an easy and reliable gastric pH measurement method by determining 13 CO2 concentration in expired air of monkeys, dogs, and rats after oral administration of Ca 13 CO3 . Methods: A correlation of 13 CO2 concentration determined by a Ca 13 CO3 breath test with gastric pH just before Ca 13 CO3 administration was analyzed in the 3 animal species. The equations and contribution ratios of regression line were calculated from logarithmic 13 CO2 concentrations at 15 min after administration of Ca 13 CO3 using the linear regression analysis. Results: The 13 CO2 concentration in the Ca 13 CO3 breath test was well correlated with the gastric pH just before Ca 13 CO3 administration in the 3 animal species ( r = −0.977 to −0.952). The equations of regression line between the 13 CO2 concentration and the gastric pH in each animal species showed good contribution ratios ( R 2 ≥ 0.89). Conclusions: The Ca 13 CO3 breath test is an informative tool to estimate gastric pH in animals and will be applicable as a new noninvasive tool for patients with GERD/PPI-resistant symptoms.